KAJIAN PENELITIAN: GAMBARAN PEMBELAJARAN E-LEARNING SAAT COVID-19 PADA SISWA SD/MI - Ningrum, Ayu Reza (STKIP PGRI Bandar Lampung, 2021)
The Covid-19 pandemic requires all activities to be carried out at home, including the education sector. In the education sector there is a change in the provision of learning through e-learning, including at the Elementary School/Madasah Ibtidaiyah (SD/MI) level. E-learning is considered one of the solutions to stop the spread of the Covid-19 virus. This study aims to find out how the description of the learning process carried out through e-learning for SD/MI students. This type of research is a literature review, meaning that it examines through the results of previous research related to e-learning in SD/MI students a number of 21 accredited national journals and highly accredited international journals. The results of the study will reveal the advantages, disadvantages in the learning that has been done. The results will also describe how the level of effectiveness during learning during the Covid-19 pandemic is. The results of the literature review can be used as a study or information as a theoretical basis for further research regarding the use of e-learning methods for elementary/MI students and developing it.